Quantitative Analysis of Biochemical Constituents in the Tissues of the Freshwater Crab, Barytelphusa Cunicularis (West-Wood, 1836) Exposed to Heavy Metal Pesticide - Atul R. Chourpagar; Rumana Shaikh; B. R. Ghorpade (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Heavy metals are toxic and subject to long-term in vivo accumulation in different aquatic species throughout the world. The purpose of the present study was to examine the quantitative analysis of biochemical constituents in the various tissues of Barytelphusa cunicularis exposed to sublethal concentration of copper sulphate (CuSO4) at 1/5th :56.4 ppm and 1/10th : 28.2 ppm for 7, 10 and 15 days. The crab has immense tolerance for wide ranging changes in the environmental factors by physiological adjustments. as compared to control. The results of the quantitative analysis show a percent (%) decrease (-) significant (P < 0.05) in the biochemical constituents in the treated crab as compared to the control.
Keywords: Barytelphusa Cunicularis; CuSO4; Biochemical constituents